PENGARUH KOMPETENSI, KEBIJAKAN INTERNAL DAN KOMITMEN KEPALA SKPK TERHADAP EFEKTIVITAS PENGGUNAAN E-PURCHASING PADA PEMERINTAHAN KABUPATEN BIREUEN - Suryani, Suryani; Iba, Zainuddin (IndOmera, 2026)
This study aims to examine the influence of competency, internal policies, and commitment of the Head of the Regional Government Work Unit (SKPK) on the effectiveness of e-purchasing. The study was conducted on SKPK Heads of the Bireuen Regency Government, using a quantitative associative method using path analysis. The results found: (1) competency significantly influences the effectiveness of e-purchasing, with a value of 55.55%. Internal policies have a 46.28% influence. And commitment has a 46.39% influence. (2) Competence, internal policies, and commitment simultaneously contribute positively to the effectiveness of e-purchasing in the Bireuen Regency Government, with a value of 87,6%. (3) There is a causal relationship between the variables of competency, internal policies, and commitment, with an average value of 5.5%.